Sistem Pengupahan Kebun Sawit dalam Perspektif Ekonomi Islam - Soleha Soleha; Saiin Saiin (AL-Muqayyad, 2020)
The purpose of this research was to determine the wages for oil palm plantations within the Islamic economic system. Descriptive qualitative with data reduction, data presentation, and conclusions drawing was applied in this study. The results showed that the oil palm plantation wage system in determining the sharing was in accordance with the Islamic Economics principles because plantation owners discussed the number of wages to be given in advance. Regarding the time of payment procedure, the owner of the oil palm plantation did not delay the payment, the wages are given directly to workers after they have finished their routine. The oil palm plantation wage system has fulfilled the value of justice because wages were distributed based on each type of work performed. However, the provision of wages has not met the eligibility value, because the stipulated wages have not been able to meet the living needs of the workers even though the wages paid were in accordance with the minimum wages’ regulation of Indragiri Hilir Regency.